The Impact of Compensation, Reputation, and E-Recruitment on Students’ Job Application Interest in State-Owned Enterprises - Khairiati Khairiati; Ahmad Rifqi; Rahmat Junaidi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of Compensation, Reputation, and E-recruitment on Job Application Interest in State-Owned Enterprises among Undergraduate Management Study Program students of Class of 2020 and 2021, University of Riau. The population in this study were students who had participated in an internship program in a State-Owned Enterprise, totaling 180 students. The number of samples in this study was carried out using the proportionate stratifield random sampling technique , which is a sampling technique that has members or elements that are not homogeneous and stratified proportionally, so that the number of samples in this study was 124 students. The results of the study with hypothesis testing showed that Compensation, Reputation, and E-recruitment simultaneously had a positive and significant effect on Job Application Interest, Compensation had a positive and significant effect on Job Application Interest, Reputation had a positive and significant effect on Job Application Interest and E -recruitment had a positive and significant effect on Job Application Interest